2021
DOI: 10.1016/j.seizure.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cannabidiol with other antiseizure medications: A narrative review

Abstract: Cannabidiol is efficacious as an adjunctive treatment in children with epilepsy associated with Dravet and Lennox-Gastaut syndromes. As its role is currently adjunctive, we reviewed the interactions of cannabidiol with other antiseizure medications (ASMs). Methods: A search of Cochrane, Pubmed and Embase databases from January 2015 to April 2020 was performed. All original research papers discussing interactions between cannabidiol and ASMs were included. Bibliographies of review articles were searched to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 36 publications
1
18
2
3
Order By: Relevance
“…However, no comparative effectiveness data exist to recommend specific antiseizure medications, everolimus, or cannabidiol over one another in a particular patient. Clinicians should be aware that both everolimus 107 and cannabidiol 108 have important drug interactions with other antiseizure medications, including with each other. 109,110 Dietary interventions, including a ketogenic diet 111,112 or low-glycemic index treatment, 113 may be an effective nonpharmacological therapy for patients with TSC with intractable epilepsy, including infantile spasms refractory to vigabatrin and hormonal therapies.…”
Section: Lungmentioning
confidence: 99%
“…However, no comparative effectiveness data exist to recommend specific antiseizure medications, everolimus, or cannabidiol over one another in a particular patient. Clinicians should be aware that both everolimus 107 and cannabidiol 108 have important drug interactions with other antiseizure medications, including with each other. 109,110 Dietary interventions, including a ketogenic diet 111,112 or low-glycemic index treatment, 113 may be an effective nonpharmacological therapy for patients with TSC with intractable epilepsy, including infantile spasms refractory to vigabatrin and hormonal therapies.…”
Section: Lungmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 8, 2022. ; https://doi.org/10.1101/2022.03.07.483344 doi: bioRxiv preprint It has been reported that CBD can increase the concentration of active metabolites of other antiseizure medications. The most robust evidence comes from CBD-clobazam interactions 36 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CBD can increase the concentration of active metabolites of other antiseizure medications. The most robust evidence comes from CBD-clobazam interactions 36 .…”
Section: Discussionmentioning
confidence: 99%
“…ESL reduces concentration of simvastatin and rosuvastatin by 54% and up to 39%, respectively [29,99,100]. CBD significantly increase levels of ESL in serum [23,25].…”
Section: Eslicarbazepinementioning
confidence: 93%